(untitled) (Global Journal of Medical Research, 2020)
Housewives in the below poverty line (BPL) families are at a high risk of suffering from malnutrition, because of poverty, and the fact that they often give priority to the nutritional needs of other family members, neglecting their own. This study has attempted to assess the nutritional status of housewives of the BPL families living in a slum in the Kidderpore area of Kolkata (India), by employing binomial tests at 5% level of significance, and using three indicators viz., body mass index or BMI, presence of angular stomatitis, and presence of pallor, and one